Manfaat Financial Thechnology Syariah terhadap Perkembangan UMKM di Kabupaten Pasuruan - Ayun, Qurrotal; Bakhri, Saiful (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Advances in information technology have brought innovation to the financial sector through Financial Technology (Fintech). In the sharia context, Sharia Fintech exists as a financial service solution based on Islamic principles designed to encourage financial inclusion and support economic growth, especially in the Micro, Small and Medium Enterprises (MSME) sector. This research aims to identify the benefits of Sharia Fintech on the development of MSMEs in Pasuruan Regency. The research was conducted using qualitative methods with a descriptive approach through data collection from observation and document analysis. The research results reveal that Sharia Fintech provides easy access to financing, increases the efficiency of financial transactions, and contributes to sharia financial literacy. Utilizing Sharia Fintech helps MSMEs expand market reach, increase productivity and maintain business sustainability in accordance with Sharia values. This research suggests increasing the application of Sharia Fintech to strengthen the sharia economic ecosystem and increase the competitiveness of MSMEs in the digital era